Motivation, meaning and well-being: Exploring gender differences and associations in participants from Iceland - Hermundur Sigmundsson; Bergsveinn Ólafsson; Michael F. Steger; Simone Grassini (Acta Psychologica)
This paper examines personal motivational factors: passion, grit, mindset and self-efficacy. The paper did also measure holistic well-being factors as: meaning in life, psychological well-being, and positive and negative affect in a population from Iceland. The sample consisted of 479 participants, including 336 females and 143 males, with an average age of 32.22 years (SD = 13.46). Personal motivational factors: General passion was measured using the Passion for Achievement scale, while grit was assessed using the Grit-S scale. Mindset was evaluated using the Theories of Intelligence Scale (TIS), and general self-efficacy was measured with the 10-item scale. Holistic well-being factors: Psychological well-being (PWB) was assessed using the Flourishing Scale, and meaning in life (MiL) was measured with three items from the Meaning in Life Questionnaire (MLQ). Positive and negative affect were evaluated using the Positive and Negative Affect Schedule (PANAS). Gender differences: The results revealed significant gender differences in two of eight variables: passion (males 4.02 vs. females 3.76) and self-efficacy (males 3.24 vs. females 3.14) favored males. Correlations: The highest correlations were observed between meaning in life and psychological well-being (r = 0.66), psychological well-being and positive affect (r = 0.58), and self-efficacy and positive affect (r = 0.54). Mindset showed the lowest correlations with other factors.The findings in the paper highlight interesting gender differences, with males scoring higher in passion, and self-efficacy. Additionally, the results suggest significant interactions between personal motivational factors (such as passion, self-efficacy, and mindset) and holistic well-being factors (such as meaning in life, psychological well-being, and positive affect).